Applying a functional approach to language development in teaching the content areas to multilingual learners in K-12 classrooms - Oliveira, Luciana C. de (Research in second language learning., 2025)
In the evolving field of Teaching English to Speakers of Other Languages (TESOL), there is a growing need for practical guidance on applying a functional approach to language development for multilingual learners (MLs) in K-12 classrooms. Applying a Functional Approach to Language Development addresses that need by focusing on the content areas of English language arts, mathematics, science, and social studies. This book offers innovative strategies for engaging students in exploring meaning in texts through classroom discussions about language. With the introduction of the new WIDA English Language Development Standards Framework (2020), the emphasis on a functional approach has become even more critical. The WIDA Standards highlight the importance of creating culturally and linguistically sustaining learning environments where MLs can thrive. The book underscores a commitment to equity for MLs by leveraging their linguistic and cultural assets, integrating content and language in collaborative settings, and making language visible as a tool for communication and a means to enact roles, through a functional approach. Grounded in systemic functional linguistics (SFL), this approach provides a metalanguage for discussing the meanings behind authors' choices and helps teachers identify language patterns to support MLs in understanding how language works. This methodology is applicable in any content classroom and is particularly vital for MLs as they expand their linguistic repertoires to engage effectively with educational content. The book is divided into two sections. Section 1 presents applied chapters that utilize a language-based approach to content instruction to design unit plans for MLs across K-12 grades. Section 2 showcases the implementation of a functional approach in teacher education programs across various states, offering valuable insights for educators. This comprehensive book aims to empower teachers with the tools and knowledge to plan effective instruction for MLs, fostering an inclusive and dynamic learning environment.